Recommendations on tourism statistics (United Nations, 1994)
Adopted by the United Nations Statistical Commission, these recommendations assist governments and businesses involved in tourism in preparing appropriate policies and programmes. The recommendations help to establish clear standards for measuring tourism. Includes the Standard International Classification of Tourism Activities (SICTA). A copublication with the United Nations.